Criminal procedure : model problems and outstanding answers - Bailey, Carlton (Model problems and outstanding answers., 2015)
In a criminal procedure class, students are asked to determine whether a citizen's constitutional rights were violated, and this question is consistently posed under a myriad of factual circumstances. In order to answer the query, students would need to examine and discuss the United States Supreme Court's interpretations of the Fourth, Fifth, Sixth, and Fourteenth Amendments of the US Constitution, identifying many tests and standards from those examinations and spirited discussions. Criminal Procedure: Model Problems and Outstanding Answers documents a few of the United States Supreme Court'